Against the rules - Suzanne, Jamie (Sweet Valley twins (Lakeville, Conn.), 1987)
Elizabeth collaborates on a school play with her friend Sophia Rizzo, even though her parents tell her to stay away from Sophia, whose brother has been in reform school.